Mapping the “Unseen” Landscape - Scott Heyes; David New; Setoki Tuiteci (Projets de Paysage)
The Aboriginal people of the South East region of South Australia, together with local and state government and universities, have recently embarked on a series of cultural revival projects to strengthen their community and to celebrate the rich heritage and connections that they maintain with the land. This paper charts the process and development of a participatory mapping project, spanning various Aboriginal homelands (but with a focus on the Boandik homeland) that was undertaken by landscape architecture lecturers and students with the collaboration and participation of the South East Aboriginal Focus Group, and non-Aboriginal groups and organisations. The paper highlights how mapping the “unseen” or intangible qualities of Aboriginal homelands in creative ways can help to communicate and educate the non-Aboriginal community about Aboriginal connections to and knowledge of the land. Through an exhibition of the maps, the project has helped to advance discussions towards the creation of an Aboriginal cultural centre in the region.